1996
DOI: 10.1095/biolreprod55.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ovine Embryos in Synthetic Oviductal Fluid Containing Amino Acids at Oviductal Fluid Concentrations

Abstract: The effects of supplementing synthetic oviductal fluid (SOF) with amino acids, at oviductal fluid concentrations, on the development of ovine in vitro-matured/in vitro-fertilized embryos was examined in three experiments. In the first, embryo development in SOF, SOF + 2% human serum (HS), SOF + 20% HS, and SOF + BSA, with and without amino acid supplementation, was examined. Development of zygotes to the blastocyst and hatching blastocyst stages was highest in medium containing 20% HS (64.8% and 54.4%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
20

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(81 citation statements)
references
References 28 publications
2
59
0
20
Order By: Relevance
“…Half of the embryos in each group were cultured in a media that contained melatonin at either a 10 -5 M concentration (embryos from the M5 and C5 oocytes) or a 10 -6 M concentration (embryos from the M6 and C6 oocytes), and the other half remained as untreated controls. The embryos from the eight groups (M5M, M5C, C5M, C5C, M6M, M6C, C6M, and C6C) were placed in a culture medium that contained SOF supplemented with essential and nonessential amino acids at oviductal concentrations (Walker et al, 1996), 0.4% BSA (w/v), 1 mM of L-glutamine, 100 IU mL -1 of penicillin G, and 100 µg mL -1 of streptomycin sulphate, covered with mineral oil, and kept at 39ºC in a maximally humidified atmosphere, with 5% CO 2 , 5% O 2 , and 90% N 2 until the blastocyst stage (day 8). The number and developmental stage of blastocysts (young, expanded, hatching and hatched blastocysts) were recorded at 6, 7, and 8 days after fertilization.…”
Section: In Vitro Fertilization and Embryo Culturementioning
confidence: 99%
“…Half of the embryos in each group were cultured in a media that contained melatonin at either a 10 -5 M concentration (embryos from the M5 and C5 oocytes) or a 10 -6 M concentration (embryos from the M6 and C6 oocytes), and the other half remained as untreated controls. The embryos from the eight groups (M5M, M5C, C5M, C5C, M6M, M6C, C6M, and C6C) were placed in a culture medium that contained SOF supplemented with essential and nonessential amino acids at oviductal concentrations (Walker et al, 1996), 0.4% BSA (w/v), 1 mM of L-glutamine, 100 IU mL -1 of penicillin G, and 100 µg mL -1 of streptomycin sulphate, covered with mineral oil, and kept at 39ºC in a maximally humidified atmosphere, with 5% CO 2 , 5% O 2 , and 90% N 2 until the blastocyst stage (day 8). The number and developmental stage of blastocysts (young, expanded, hatching and hatched blastocysts) were recorded at 6, 7, and 8 days after fertilization.…”
Section: In Vitro Fertilization and Embryo Culturementioning
confidence: 99%
“…The matured oocytes were divided into two groups and fertilized in vitro, as described by Walker et al (1996) with some modifications. In vitro fertilization was performed in four-well Petri dishes (Nunclon; Nalge Nunc International, Kamstrup, Denmark) by depositing 20-30 oocytes into 500 µL of semen suspension (1 × 10 6 spermatozoa mL −1 ) derived from the two experimental culture systems (SOF and 0.6% (w/v) BSA), with or without SOD, as described earlier.…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
“…Paraffin oil [10][11][12], mineral oil [13][14][15] and silicone oil [16,17] have been broadly used to protect culture medium from evaporation and contamination when early embryos are cultured. Further studies have indicated that the application of oil affects the embryo development either in a positive or a negative way [18,19].…”
Section: Introductionmentioning
confidence: 99%